2017
DOI: 10.1016/j.psychres.2017.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neurocognitive function in major depressive disorder, bipolar disorder, and schizophrenia in later life: A cross-sectional study of euthymic or remitted, non-demented patients using the Japanese version of the Brief Assessment of Cognition in Schizophrenia (BACS-J)

Abstract: Major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia (SZ) are associated with cognitive dysfunction both in adulthood and in later life. In this study, we directly compared neurocognitive function between these three conditions in later life, employing stringent definitions of euthymia and symptomatic remission. Cognitive function in 60 elderly outpatients with MDD, BD, or SZ (20 patients per group) was assessed using the Japanese version of the Brief Assessment of Cognition in Schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
7
27
1
Order By: Relevance
“…The magnitude of cognitive dysfunction was compatible to which reported in a previous study (using BACS to assess cognitive function among MDD patients, Fig. 1A) (Terachi et al., 2017). We also compared our results with previous studies with bipolar disorder and schizophrenia patients conducting BACS tests (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The magnitude of cognitive dysfunction was compatible to which reported in a previous study (using BACS to assess cognitive function among MDD patients, Fig. 1A) (Terachi et al., 2017). We also compared our results with previous studies with bipolar disorder and schizophrenia patients conducting BACS tests (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…1B). Similar degrees of cognitive impairments were observed in patients with bipolar disorder and schizophrenia patients, while patients with MDD may exhibited smaller impairments in several neurocognitive domains compared to patients with either of the other two disorders (Terachi et al., 2017).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Differences of node strength centrality between FES-related and MDD-related cognitive functions included general intelligence, motor speeding, perceptual sensitivity, visual and pattern recognition memory, shifting, planning, sustained attention and inhibition, working memory, and strategy. Consistent with previous studies, patients with FES had more impairments in premorbid IQ, memory, attention, processing speed, and learning than patients with MDD [22][23][24]. Neuroimaging studies have demonstrated that patients with schizophrenia have more severe deficits in prefrontal and superior temporal activation during the performance of working memory tasks [25,26].…”
Section: Discussionsupporting
confidence: 84%
“…It consists of various tests that assess the following six cognitive domains: verbal memory, working memory, motor speed, verbal fluency, attention and speed of information processing, and executive function. The BACS was originally developed for patients with schizophrenia, but has also been used for those with bipolar disorder 34 , 35 , and recently for those with MDD 36 , 37 . Importantly, the use of this comprehensive battery consisting of highly reliable and valid tests that were selected specifically for their tolerability in patients with various psychiatric disorders, will facilitate comparisons across numerous studies.…”
Section: Introductionmentioning
confidence: 99%